Basic marketing : - McCarthy, E Jerome (Richard D. Irwin, 1960)
Basic Marketing and the supporting materials that accompany it have been more widely used than any other teaching materials for introductory marketing. Consistent with our belief in continuous quality improvement, this edition has been critically revised, updated, and rewritten to reflect new concepts, new examples, and recent 'best practices'. This edition extends the strategy planning approach, integrating concepts tightly with the marketing strategy planning model.